Pengaruh Citra Merek dan Potongan Harga terhadap Kepuasan serta Dampaknya terhadap Niat Beli Ulang Produk Fashion pada Shopee: Studi pada Pelanggan Online Shop Shopee di Semarang - Anif Maharyani Ayuningtyas; Endang Tjahjaningsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The fashion industry has grown rapidly, and the rise of e-commerce has made it easier for consumers to buy fashion products online. Many consumers shop online through Shopee. This study aims to determine the effect of brand image and discounts on satisfaction and their impact on repurchase intentions for fashion products on Shopee. The sample of this study was 100 Shopee application users in the city of Semarang with a purposive sampling methodology. The research method used is a quantitative method. Hypothesis testing uses multiple linear regression using statistical-based data, namely SPSS. The results of this study indicate that brand image has a positive and significant effect on satisfaction, discounts have a positive and significant effect on satisfaction and satisfaction has a positive and significant effect on repurchase intentions.